Diagnostic accuracy of molecular amplification tests for human African trypanosomiasis--systematic review. - Claire M Mugasa; Emily R Adams; Kimberly R Boer; Heleen C Dyserinck; Philippe Büscher; Henk D H F Schallig; Mariska M G Leeflang (PLoS Neglected Tropical Diseases)
Background A range of molecular amplification techniques have been developed for the diagnosis of Human African Trypanosomiasis (HAT); however, careful evaluation of these tests must precede implementation to ensure their high clinical accuracy. Here, we investigated the diagnostic accuracy of molecular amplification tests for HAT, the quality of articles and reasons for variation in accuracy. Methodology Data from studies assessing diagnostic molecular amplification tests were extracted and pooled to calculate accuracy. Articles were included if they reported sensitivity and specificity or data whereby values could be calculated. Study quality was assessed using QUADAS and selected studies were analysed using the bivariate random effects model. Results 16 articles evaluating molecular amplification tests fulfilled the inclusion criteria: PCR (n = 12), NASBA (n = 2), LAMP (n = 1) and a study comparing PCR and NASBA (n = 1). Fourteen articles, including 19 different studies were included in the meta-analysis. Summary sensitivity for PCR on blood was 99.0% (95% CI 92.8 to 99.9) and the specificity was 97.7% (95% CI 93.0 to 99.3). Differences in study design and readout method did not significantly change estimates although use of satellite DNA as a target significantly lowers specificity. Sensitivity and specificity of PCR on CSF for staging varied from 87.6% to 100%, and 55.6% to 82.9% respectively. Conclusion Here, PCR seems to have sufficient accuracy to replace microscopy where facilities allow, although this conclusion is based on multiple reference standards and a patient population that was not always representative. Future studies should, therefore, include patients for which PCR may become the test of choice and consider well designed diagnostic accuracy studies to provide extra evidence on the value of PCR in practice. Another use of PCR for control of disease could be to screen samples collected from rural areas and test in reference laboratories, to spot epidemics quickly and direct resources appropriately.